Kualifikasi Guru, Sarana Prasarana dan Teknologi: Systematic Literature Review tentang Dampaknya terhadap Hasil Belajar Siswa yang Berkelanjutan - Tuanany, Nursyahar Jihan; Timan, Agus; Triwiyanto, Teguh (Jurnal Pendidikan dan Teknologi Indonesia, 2025)
This study aims to analyze the extent to which teacher qualifications, infrastructure and technology affect student learning achievement. This research used the Systematic Literature Review (SLR) method to draft the literature review. Data was obtained from articles published within 6 years (2019-2024) collected from ScienceDirect and Google Scholar using the keywords “Teacher Qualification”, “School Infrastructure”, “School Facilities”, “Technology”, “Student Achievement”. The findings indicate that these three factors consistently play a crucial role in enhancing the quality of student learning outcomes. Teacher qualifications are correlated with improved student understanding and academic performance. Adequate educational infrastructure contributes to the creation of a supportive learning environment that fosters active student engagement. Meanwhile, the integration of technology into learning has been shown to enrich the learning experience and facilitate content comprehension. These findings underscore the significance of all three aspects in shaping a sustainable and responsive education system in the face of 21st century challenges.